Examining the Relationship Between School Principals' Job Satisfaction and Burnout Levels (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the relationships between school principals' job satisfaction levels and their burnout levels (emotional exhaustion, depersonalization, and personal accomplishment). The study was conducted on a total of 109 school principals working in the Mamak and Altındağ districts of Ankara province and the Süleymanpaşa district of Tekirdağ province. The study was designed based on the correlational survey model, one of the quantitative research methods. The Job Satisfaction Scale and the Maslach Burnout Inventory were used as data collection tools in the study. The data obtained were analyzed using the SPSS 25.0 statistical package program. Descriptive statistics, normality tests, the t-test for independent samples, one-way analysis of variance (ANOVA), Pearson correlation analysis, and multiple linear regression analysis techniques were used in the analysis process. The research findings revealed that there were significant and negative relationships between school principals' job satisfaction and burnout levels. It was determined that job satisfaction, particularly in terms of salary, supervision, and internal communication, significantly predicted emotional exhaustion and depersonalization levels. In addition, it was found that the working conditions and rewards sub-dimension positively affected school principals' perceptions of personal success. In terms of demographic variables, no significant difference was found based on gender; however, significant differences were found in some job satisfaction and burnout sub-dimensions based on age and type of school. In conclusion, the research findings show that increasing school principals' job satisfaction plays an important role in reducing their burnout levels. In this context, it is recommended that organizational arrangements supporting the psychological well-being of managers in educational institutions be developed.